Recent Deflection Effects of Macro Components in G7 Countries and Contractionary Monetary Expansion Fact - Özker, Ahmet Niyazi (Archives of Business Research, 2022)
This study discussed the standard criteria points that constitute the reasons for monetary expansion, primarily based on seven countries representing the G7 countries, this expansion in the monetary base brought up a structural relationship model. The fact that frequently brought up the macro fluctuations has been a crucial place as interest rates, unemployment rates and exchange rates variability as the main macro components recently. The effects of these components on economic growth have also provided an important justification for evaluating their recent significant deviations. It is seen that the commonwealth of wealth and economy of the G7 countries in the world constitutes approximately 68 per cent. In this respect, all kinds of targets for economic growth also represent a structure that targets global trade and global trade at significant scales to national income contribution values, albeit nominally. This case also shows why a balanced policy towards increasing interest rates in the recent period and an interest policy compatible with global exchange rate policies are frequently kept on the agenda. This current approach has caused different monetary policies to come to the fore, especially in these countries with a high level of wealth. Essential goals have emerged to reduce costs and turn the growing monetary base into a seigniorage income. These targets pushed the scale effect concerning monetary expansion based on these macro components to an economic growth-based projection.